1980
DOI: 10.1037/0096-1523.6.1.24
|View full text |Cite
|
Sign up to set email alerts
|

A further parallel between selective adaptation and contrast.

Abstract: It is generally believed that selective adaptation effects in speech perception are due to a reduction in sensitivity of auditory feature detectors. Recent evidence suggest that these effects may derive instead from contrast. In a further test of the contrast hypothesis, we conducted two experiments each involving both adaptation and contrast sessions with matching stimulus sets. During the adaptation sessions of Experiment 1, subjects identified two series of velar stimuli varying in voice onset time, [ga]-[k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
36
1
1

Year Published

1981
1981
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 34 publications
0
36
1
1
Order By: Relevance
“…Diehl and his co-workers (e.g., Diehl et al, 1978;Diehl et al, 1980;Elman, 1979) have presented evidence to suggest that the speech adaptation effects typically obtained with procedures similar to that employed here do not reflect fatigue introduced into those sensory processes engaged by an adapting stim…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Diehl and his co-workers (e.g., Diehl et al, 1978;Diehl et al, 1980;Elman, 1979) have presented evidence to suggest that the speech adaptation effects typically obtained with procedures similar to that employed here do not reflect fatigue introduced into those sensory processes engaged by an adapting stim…”
Section: Discussionmentioning
confidence: 99%
“…However, because the effect is not eliminated, a further component remains to be explained. That component could result from the operation of processes such as response biases (Diehl, Elman, & McCusker, 1978;Diehl, Lang, & Parker, 1980), or holistic syllable adaptation (Darwin, 1976), or, indeed, adaptation at a phonetic level of analysis. Alternatively, it may be attributable to the failure to completely eliminate spectrotemporal contiguity between adaptors and testsyllables, The alternative strategy for achievingthe dissociation -that of creating stimuli with identical acoustical specifications that are nonetheless identified in different phonetic categories-has also been explored.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Anderen hebben daarentegen beargumenteerd dat selectieve adaptatie mogelijk een relatief simpele criterium verschuiving weerspiegelt (Diehl, 1981;Diehl et al, 1978;Diehl et al, 1980). In tegenstelling tot recalibratie, is selectieve adaptatie niet afhankelijk van een AV conflict maar in plaats daarvan wordt het gehele effect bepaald door het auditieve segment van de stimulus zoals bevestigd in onderzoek naar selectieve adaptatie in AV spraak (Roberts & Summerfield, 1981;Saldaña & Rosenblum, 1994;Shigeno, 2002).…”
Section: Nederlandse Samenvatting Summary In Dutchunclassified
“…Macmillan, Goldberg, and Braida (1988) have argued that some stimuli along a dimension play a special role in providing a reference point that is used in the contextual coding of other stimuli. Both category boundaries (e.g., Diehl, Lang, & Parker, 1980) and prototypes (Samuel, 1982) have been suggested as critical. We chose distance from the categorical /ba/-/pa/ boundary as such a reference point, since Samuel demonstrated that for VOT stimuli like ours, distance from the boundary accounted for se-lective adaptation effects.…”
mentioning
confidence: 99%